2004
DOI: 10.1179/135100004225006812
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione reductase is expressed at high levels in pancreatic islet cells

Abstract: Reactive oxygen species are, at least partly, involved in the diabetogenic agent-induced dysfunction of pancreatic beta-cells because the expression of antioxidative and redox proteins is low. We examined the levels of antioxidant/redox proteins, peroxiredoxins-1, -4, and -6 and glutathione reductase (GR), by immunohistochemistry and found that the expression of GR was very high in pancreatic islet cells compared to exocrine cells. When diabetes was induced by an intravenous injection of streptozotocin, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
1
6
0
2
Order By: Relevance
“…Considering tissue mass, the total content of Prx-4 is highest in the liver, and thus it is more likely that the supply of the protein to the blood largely depends on the liver. As previously described, Prx-4 appears to be highly expressed in exocrine pancreas rather than islets (37), and another study also reported that another Prx isoform is highly expressed in pancreatic islet cells (38). Consistent with these findings, it would be reasonable that no significant alteration of Prx-4 levels in the serum would be observed in the experiments using streptozotocininduced diabetic rats.…”
Section: Discussionsupporting
confidence: 77%
“…Considering tissue mass, the total content of Prx-4 is highest in the liver, and thus it is more likely that the supply of the protein to the blood largely depends on the liver. As previously described, Prx-4 appears to be highly expressed in exocrine pancreas rather than islets (37), and another study also reported that another Prx isoform is highly expressed in pancreatic islet cells (38). Consistent with these findings, it would be reasonable that no significant alteration of Prx-4 levels in the serum would be observed in the experiments using streptozotocininduced diabetic rats.…”
Section: Discussionsupporting
confidence: 77%
“…These enzymes often contain a CXXC redox active dithiol motif and catalyze thiol-disulfide exchange reactions with different substrate specificities. In particular, Trx and Grx systems are generally described as protein disulfide reductants and are assigned an “antioxidant” function [99–101]. More recently, Srx, a monothiol enzyme, was shown to reduce glutathionylated proteins.…”
Section: Leadmentioning
confidence: 99%
“…The endogenously produced hydrogen peroxide is reduced by reduced glutathione (GSH) in the presence of GSHPx (Świderska-Kołacz, Klusek, & Kołątaj, 2007). However, the intracellular GSH level is maintained in the reduced form by the NADPH-requiring enzyme glutathione reductase (Nagaoka, Iuchi, Ikeda, & Fujii, 2004). Therefore, changes in glutathione reductase activity are particularly important because the enzyme substitutes the reduced form of glutathione during NADPH oxidation, when high amounts of glutathione disulphide are formed in the cell.…”
Section: Blood Serum and Muscle Oxidative Statusmentioning
confidence: 99%